Mufradāt al-Kitāb al-Arabiyyah Li an-Najāh ‘Inda Naẓariyyah ‘Abd ar-Rahmān Ibn Ibrāhim al-Fauzān - Nuruddin, Ahmad; Rosyidi, Abdul Wahab; Sodik, Achmad Ja’far; Rufaiqoh, Elok (Prodi Pendidikan Bahasa Arab FTK UIN Sunan Ampel, 2024)
Purpose– Vocabulary is one of the main keys to being able to learn a foreign language because without vocabulary learning a foreign language will be very difficult to implement. Among the learning resources are books that also study vocabulary, with various presentations. However, the system for presenting vocabulary in books still requires a deeper review in terms of the concept of presentation. Design/Methodology/Approach– Through mixed methods based on literature studies, this article reveals how the concept of presenting vocabulary in Abdur Rahman bin Ibrahim Al-Fauzan's perspective book. The data is processed from the book